Efficacy analysis and prognostic factors of first-line chemotherapy combined with immunotherapy in extensive-stage small cell lung cancer: a real-world study - Jian-Xi Zhou; Yun-Chuan Sun; Li Xiao; Hong-Ling Lu; Xiao-Ming Yin; Kui Fan; Ying-Nan Zhou (Scientific Reports)
Abstract Extensive-stage small cell lung cancer (ES-SCLC) is a highly aggressive subtype of lung cancer with limited treatment options and poor prognosis. In recent years, immune checkpoint inhibitors (ICIs) combined with chemotherapy have demonstrated significant efficacy in several clinical trials. This study aims to evaluate the efficacy of first-line chemotherapy combined with immunotherapy in patients with ES-SCLC and identify prognostic factors based on real-world data. This retrospective study analyzed the clinical data of 349 patients with ES-SCLC treated at Cangzhou Hospital of Integrated Traditional Chinese and Western Medicine from January 2018 to August 2023. The patients were divided into a combination group (chemotherapy plus immunotherapy, n = 173) and a chemotherapy group (chemotherapy alone, n = 176) based on their treatment regimens. The primary endpoints were overall survival (OS) and progression-free survival (PFS), and the secondary endpoint was treatment-related adverse events. Kaplan–Meier survival analysis was performed, and Cox regression models were used to analyze the factors influencing OS and PFS. The median OS in the combination group was 14.9 months, significantly longer than 11.9 months in the chemotherapy group (P < 0.001). After applying Propensity Score Matching (PSM) to minimize selection bias, the survival advantage remained statistically significant. The 1-, 2-, and 3-year OS rates in the combination group were 62.4%, 42.8%, and 19.5%, respectively, compared to 50.2%, 20.8%, and 9.6% in the chemotherapy group. The median PFS in the combination group was 5.4 months, also significantly longer than the 3.8 months observed in the chemotherapy group (P < 0.001). Multivariate analysis identified chemotherapy alone, ECOG performance status, and number of metastatic sites as independent risk factors for poorer OS and PFS (P < 0.001). A separate analysis was conducted to evaluate the association between tumor response (CR/PR/SD/PD) and survival outcomes, which showed that patients with CR/PR had significantly better OS and PFS compared to those with SD/PD (P < 0.001). These findings reinforce the clinical importance of achieving tumor response. There were no significant differences in the incidence of adverse events between the two groups, with most adverse events being grade 1–2, and no grade 5 adverse events were reported. This study demonstrates that chemotherapy combined with immunotherapy significantly prolongs OS and PFS in patients with ES-SCLC without substantially increasing treatment-related adverse events. This combination therapy shows promising clinical value for improving long-term prognosis in ES-SCLC patients. Future studies should explore potential biomarkers to optimize individualized treatment strategies.